2020
DOI: 10.3390/toxins12060377
|View full text |Cite
|
Sign up to set email alerts
|

Zearalenone (ZEN) in Livestock and Poultry: Dose, Toxicokinetics, Toxicity and Estrogenicity

Abstract: One of the concerns when using grain ingredients in feed formulation for livestock and poultry diets is mycotoxin contamination. Aflatoxin, fumonisin, ochratoxin, trichothecene (deoxynivalenol, T-2 and HT-2) and zearalenone (ZEN) are mycotoxins that have been frequently reported in animal feed. ZEN, which has raised additional concern due to its estrogenic response in animals, is mainly produced by Fusarium graminearum (F. graminearum), F. culmorum, F. cerealis, F. equiseti, F. crookwellense and F. semitectums… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
91
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 118 publications
(160 reference statements)
4
91
1
11
Order By: Relevance
“…As shown in this figure, α-ZAL, β-ZAL, and ZAN were not detected, and these analytes were never found in any of the samples. These results are in agreement with a review of the literature, which revealed that ZAN and ZALs have never been characterized in avian species [ 6 , 7 ].…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…As shown in this figure, α-ZAL, β-ZAL, and ZAN were not detected, and these analytes were never found in any of the samples. These results are in agreement with a review of the literature, which revealed that ZAN and ZALs have never been characterized in avian species [ 6 , 7 ].…”
Section: Resultssupporting
confidence: 92%
“…Because of the strong SSE, the low SNR, and the low RE observed for β-ZOL in liver with method 1, and because a review of the literature revealed that α-ZAL, β-ZAL, and ZAN are not reported as being formed in avian species, it was decided that method 2 would be used to quantify α-ZOL, β-ZOL, and ZEN, while method 1 would be used to detect the presence or absence of α-ZAL, β-ZAL, and ZAN [ 6 , 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations